2021
DOI: 10.1111/jfb.14686
|View full text |Cite
|
Sign up to set email alerts
|

Brown trout phylogenetics: A persistent mirage towards (too) many species

Abstract: Funding informationM. Oral was supported by a visiting grant from the MUSE "Explore" programme, publicly funded through the ANR (French National Research Agency) under the "Investissements d'avenir" program (ANR-16-IDEX-0006) and the Erasmus+ program of the European Union."… such abundant literature and insightful studies may be little more than a mirage".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 135 publications
(233 reference statements)
0
18
0
Order By: Relevance
“…Phylogenetic uncertainty stemming from vast intraspecific variation is not unique to the discussion of Brook Trout taxonomy and has long been part of conversations related to the conservation of Salvelinus and other stream salmonids (Guinand et al, 2021). Repeated radiation through increasingly diverse environments has led to significant uncertainty in how to appropriately classify the extensive taxonomic and functional diversity in many species of Salvelinus (Reist et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic uncertainty stemming from vast intraspecific variation is not unique to the discussion of Brook Trout taxonomy and has long been part of conversations related to the conservation of Salvelinus and other stream salmonids (Guinand et al, 2021). Repeated radiation through increasingly diverse environments has led to significant uncertainty in how to appropriately classify the extensive taxonomic and functional diversity in many species of Salvelinus (Reist et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several species concepts with no consensus decision has resulted in inflated taxonomic identifications (23 species according to IUCN, 2020; 30-35 species according to Kottelat & Freyhof, 2007;Sanz, 2018 andup to 60 species according to Behnke, 1986;Jonsson & Jonsson, 2011;Froese & Pauly, 2019). However, the most recent opinion paper by Guinand, Oral & Tougard, (2021), discussed thoroughly that phenotypic and genotypic diversity of brown trout is best explained in the concept of species complex and indicates multiple trout species.…”
Section: Discussionmentioning
confidence: 99%
“…However, salmon taxonomy is still confusing and problematic. In recent years, there are lots of studies about biogeography, phylogeny, phylogeographic and systematic position of Salmo species (Bardakci et al, 2006;Sušnik et al, 2006;Kanjuh et al, 2020;Guinand et al, 2021). Rossi et al (2019) investigated the genetic identification of native populations of S. trutta complex in central Italy and found that most of the haplotypes observed belong to the Adriatic or Mediterranean lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, reported 14 Salmo species from the inland waters of Turkey. Guinand et al (2021) indicated that the delimitation of trout taxa by ichthyologists was certainly first impacted by the poor awareness of phenotypic plasticity and speciation as a process, then based on species concepts based on diagnosability, while these taxa are not reproductively isolated and contradict Mayr's (1942) biological species concept.…”
Section: Discussionmentioning
confidence: 99%